The tragic week in Barcelona (1909) in school historiography: from Africanism to postmodernity - Castillejo Cambra, Emilio (Historia y Memoria de la Educación, 2019)
The treatment of the events of the Tragic Week of Barcelona in 1909 that school historiography presented before 1975 (the end of Franco’s dictatorship), was conditioned by various factors: sacralization of the social order and the Restoration system, Africanism and, ecclesiastic thought. From this date on, in spite of the advances in professional historiography and democratic freedoms, we have verified that history textbooks still do not provide the keys necessary for demonstrating the complicities that upheld the power system - against which the revolt took place in Barcelona in July 1909 - nor the ideologies that served to legitimize the uprising: anti-colonialism, anti-capitalism, anti-militarism and anti-clericalism. In this concealment there is evidence of reminiscences of the past (catch-words from ecclesiastic thought, militarism, colonialism...), social taboos about the Catholic Church and the Army, and the liquidity and lack of commitment of the prevailing postmodern thought.